2017
DOI: 10.5194/angeo-35-721-2017
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric loss from the dayside open polar region and its dependence on geomagnetic activity: implications for atmospheric escape on evolutionary timescales

Abstract: Abstract. We have investigated the total O + escape rate from the dayside open polar region and its dependence on geomagnetic activity, specifically Kp. Two different escape routes of magnetospheric plasma into the solar wind, the plasma mantle, and the high-latitude dayside magnetosheath have been investigated separately. The flux of O + in the plasma mantle is sufficiently fast to subsequently escape further down the magnetotail passing the neutral point, and it is nearly 3 times larger than that in the days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(89 citation statements)
references
References 51 publications
(68 reference statements)
16
69
0
Order By: Relevance
“…This result is consistent with Yau et al (1988), who showed a Kp dependence on the O + flux at lower altitudes, and with Slapak et al (2017), who studied the oxygen ion escape from the plasma mantle and cusp and its dependence on the geomagnetic activity. Slapak et al (2017) found that in the plasma mantle and the dayside magnetosheath, the scaled O + outflow increases exponentially as exp(0.45Kp). In the plasma mantle, they observed an increase of 1.5 orders of magnitude for the scaled oxygen ion outflow between average conditions (Kp ≈ 3) and highest geomagnetic activities.…”
Section: Geomagnetic Activitysupporting
confidence: 91%
See 4 more Smart Citations
“…This result is consistent with Yau et al (1988), who showed a Kp dependence on the O + flux at lower altitudes, and with Slapak et al (2017), who studied the oxygen ion escape from the plasma mantle and cusp and its dependence on the geomagnetic activity. Slapak et al (2017) found that in the plasma mantle and the dayside magnetosheath, the scaled O + outflow increases exponentially as exp(0.45Kp). In the plasma mantle, they observed an increase of 1.5 orders of magnitude for the scaled oxygen ion outflow between average conditions (Kp ≈ 3) and highest geomagnetic activities.…”
Section: Geomagnetic Activitysupporting
confidence: 91%
“…In the plasma mantle, they observed an increase of 1.5 orders of magnitude for the scaled oxygen ion outflow between average conditions (Kp ≈ 3) and highest geomagnetic activities. In comparison with Slapak et al (2017, their Fig. 4), who show the distribution of O + observations over Kp for the plasma mantle and the dayside magnetosheath, we estimate a lower scaled O + outflow, which is reasonable because our region of observations is in the polar cap.…”
Section: Geomagnetic Activitysupporting
confidence: 85%
See 3 more Smart Citations